Empowerment of The Posyandu Kenari Partner Group in The Village of Angar in Kosabangsa Program for The Prevention of Stunting : Pemberdayaan Kelompok Mitra Posyandu Kenari Desa Angar Dalam Program Kosabangsa untuk Pencegahan Stunting - Siahaya, Griennasty Clawdya; Wilma Fransisca Mamuly; Lea Mediatrix Janwarin; Febby Jeanry Polnaya; Helen C.D.Tuhumury; Diana Julaidy Patty (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting is one of the malnutrition problems in Indonesia that has become a serious concern for the government. The geographical condition factor, which is located in underdeveloped areas and categorized as an area of extreme poverty, is one of the factors for the high stunting rate in East Seram Regency region, especially in Angar village. The Posyandu Kenari group is one of the target partner groups for community service activities in the Kosabangsa program. The Kosabangsa program aims to intervene through the application of technology and innovation provided in answering the nutritional problems that occur in children under five in Angar Village as a preventive measure against stunting. For this reason, the solution provided through the DRTPM-Kemdikbudristek Kosabangsa Funding Program in 2024 collaboration between the UKIM Implementation Team and the UNPATTI Assistance Team together provides interventions to partners in the form of Health education on stunting in young children and prevention efforts, dissemination of the use of local foods made from sago in MP-ASI processing, training on MP-ASI processing made from sago flour (sago noodles and modified sago biscuits), establishment of Paparisa Stunting Corner at Posyandu Kenari, and installation of health education media in public places. The method of implementing this PkM activity starts from the preparation, implementation and monitoring and evaluation phases for the partners. The results obtained through the interventions provided showed that there was an increase in knowledge for partners which had an impact on behavior change, partners were able to process MP-ASI from sago starch raw materials with moringa leaf substitution, a stunting corner was created as a source of information on stunting problems and also a place for intervention in monitoring supplementary feeding.